A textbook of postpartum hemorrhage a comprehensive guide to evaluation, management and surgical intervention - B-Lynch, Christopher (Sapiens, 2006)
Postpartum hemorrage is a major cause of maternal mortality - especially in the developing world. Estimates vary but it can confidently be stated that well over 250,000 women die as a result of the condition every year. Many of these deaths could be prevented by better and more appropriate treatment, delivered within a time-critical framework. The objective of this book is to bring together within a single volume the most up to date information about the epidemiology, diagnosis and management of postpartum hemmorrhage. Whilst much has been published on the subject a truly comprehensive synthesis of this kind has never before been attempted. This volume sets out, therefore, to provide physicians with an overall clinical perspective that has hitherto been unavailable. The volume is essentially practical in orientation addressing specific issues that confront any obstetrician responsible for the management of postpartum hemorrhage. In particular it features new surgical techniques that have been shown to be markedly successful and straigh forward to apply, and which have clear advantages over emergency hysterectomy in many instances. Other important issues that are reviewed in detail include causation, prevention, therapy for atonic and non-atonic conditions, and long term consequenses Written by an international team of specially invited experts, this book should meet a genuine need. In particular it is hoped it will contribute in a practical way to management of postpartum hemorrhage in developing countries where scarcity of resources may be compounded by a lack of clinically reliable information about the last theraputic advances.